1999
DOI: 10.1007/s11627-999-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro rooting of sentang shoots (Azadirachta excelsa L.) and acclimatization of the plantlets

Abstract: In vitro proliferated sentang shoots were cultured onto half-strength Mnrashige and Skoog (MS) medium containing combinations of 1-naphthyleneacetic acid (NAA) and indole-3-butyric acid (IBA). Sentang shoots were unable to root in the absence of both auxins. A combination of 0.5 mg NAA per and 1 mg IBA per I induced the most shoots to form roots. With the addition of 2.5 g activated charcoal per 1 into half-strength MS medium containing 0.5 mg NAA per l and 1 mg IBA per 1, roots were more numerous and longer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
2
9
0
Order By: Relevance
“…Rooting frequencies of 97.7% were obtained after the regenerated shoots were transferred to medium containing 0.5 mg/L indole butyric acid (IBA) and 200 mg/L Cef. Adding a lower concentration of sucrose to the rooting media was more beneficial for root induction, consistent with previous studies (Kooi et al, 1999). Frequency of root regeneration was defined as the number of rooted plantlets out of total number of regenerated plants.…”
Section: Optimization Of Factors Affecting Gus Expression and Hygromysupporting
confidence: 82%
See 1 more Smart Citation
“…Rooting frequencies of 97.7% were obtained after the regenerated shoots were transferred to medium containing 0.5 mg/L indole butyric acid (IBA) and 200 mg/L Cef. Adding a lower concentration of sucrose to the rooting media was more beneficial for root induction, consistent with previous studies (Kooi et al, 1999). Frequency of root regeneration was defined as the number of rooted plantlets out of total number of regenerated plants.…”
Section: Optimization Of Factors Affecting Gus Expression and Hygromysupporting
confidence: 82%
“…Ahmed et al (1998) reported that root establishment in transgenic shoots requires a great deal of labor and time. A previous study reported that because half-strength media has reduced ionic strength, it is more beneficial for regenerated shoot rooting (George, 1996;Upreti and Dhar, 1996;Kooi et al, 1999). To identify the optimal medium for root formation, we tested thirteen medium compositions (Table 3).…”
Section: Optimization Of Factors Affecting Gus Expression and Hygromymentioning
confidence: 99%
“…There is substantial evidence that auxins play a crucial role on adventitious root formation and that the exogenous auxins required for the initiation of roots tend to inhibit root elongation (de Klerk et al 1999). Moreover, different plant species might vary in their requirement of auxin type for adventitious root formation (Kooi et al 1999). When testing the effect of basal medium and several auxins (IAA, IBA and NAA) at 1 and 2 mg l À1 (Figure 2), highest rooting frequency of D. lusitanicum shoots (57%) was observed in 1/2MS medium supplemented with 1 or 2 mg l À1 NAA (p<0.05) However, on NAA containing media, rooting was accompanied by callusing at the base of the shoots and the roots formed were short.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the high gas permeability of the film, the aerial environment inside this culture vessel is improved through natural ventilation between the inside and outside air. The CP system was shown to be suitable for growth under CO 2 enriched conditions with a low PPF at 45 lmol m -2 s -1 on sugar-free medium and rock-wool multi-block or agar substrates for Spathiphyllum (Tanaka et al 1992), Eucalyptus (Nagae et al 1996), Azadirachta excelsa (Kool et al 1999), banana (Musa spp.) (Nhut et al 2002), and strawberry (Nhut et al 2003).…”
Section: Natural Ventilation Of Small Culture Vesselsmentioning
confidence: 99%